Serum Ferritin Level as a Prognostic Marker of 30 days In Hospital Mortality of Coronavirus Disease 2019 (COVID 19) Pneumonia at World Citi Medical Center: A Retrospective, Observational Cohort, Single Center Study - M. Quirit Allen; Sorreda Jayson; Pinera Rizalyn; Kate Tobias Karen (International Journal of Coronaviruses, 2021)
Introduction The COVID-19 pandemic continues to affect a large swath of the global population. The Philippine records four hundred seventy-four thousand sixty-four (474, 064) confirmed COVID 19 cases since December 31 2020. The COVID 19 pandemic recently highlighted the role of systemic hyperferritenemia as a major cause of death. In this study, we were able to correlate the serum ferritin level and predict 30 day in hospital mortality in COVID 19 pneumonia. Objective The aim of the study is to investigate the correlation between serum ferritin level and disease mortality in COVID19 pneumonia with subset analysis on demographics and co-morbidities of patients with COVID 19 pneumonia. Methodology We reviewed the records of all laboratory confirmed COVID 19 patients from World Citi Medical Center from April 2020 up to April 2021.A statistically significant sample size of seventy nine (79) admitted patients were used in this study. A serum ferritin level was assayed using electrochemilumenescence immunoassay with a Roche COBAS analyzer. Results Result showed that high ferritin level is associated with in hospital mortality. With ferritin level of 1437.07ng/ml, poor clinical outcome and in hospital mortality was considered. We also observed that demographics and co morbidities of patients in this study were significant to predict in hospital mortality. Further sub-analysis of co morbidities such as Hypertensive cardiovascular disease, Type 2 Diabetes Mellitus, Chronic kidney disease, Liver disease, Chronic obstructive pulmonary disease and Cerebrovascular disease showed poor outcome which were directly related to ferritin levels with p value of <0.0001. Conclusion This study has demonstrated that elevated ferritin levels were shown to correlate with 30 day in hospital mortality as well as medical comorbidities such as Hypertensive Cardiovascular disease, Type 2 Diabetes Mellitus, and chronic kidney disease have shown significant evidence for in hospital mortality.
Keywords: Serum Ferritin